Literature Review : Pengaruh Jenis Air Terhadap Pertumbuhan Larva Nyamuk Aedes aegypti di Indonesia - Aroonasyaka, Rama (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2025)
The World Health Organization (WHO) reported that 2.2 million cases of Dengue Hemorrhagic Fever occurred in 2010, but this number increased to 3.2 million in 2015. The Indonesian Ministry of Health reported that in 2022 there will be 95,893 cases of dengue fever causing death in 219 Regencies/Cities in Indonesia. This research uses a systematic literature review method using scientific databases. Aedes aegypti larvae can grow in various type of water, according to five studies that examined Aedes aegypti larvae in various water characteristics. Aedes aegypti can grow well in water mixed with acidic peat, water around the coast which has high salinity levels, brackish water and sea water. The conclusion is that Aedes aegypti larvae can grow in various types of water, however, salinity, pH, environmental temperature and various other factors influence the growth rate of larvae